Teacher Talk: Student’s Perception and Expectation - Nur Mutmainna Halim; Yasinta Wulandari; Abd Halim (ELT Worldwide: Journal of English Language Teaching, 2021)
Teacher talk undoubtedly makes a certain factor whether the class will meet objectives of teaching and learning process or not. This research investigated (1) students’ perception towards teacher talk that happened during the teaching and learning process, and (2) students’ ideal expectations about their English teacher. This was a descriptive qualitative research. One English teacher and one class of first year senior high students were engaged in the research. The data of this research were collected from transcribed-classroom video recording and interview to some students. The results indicated that (1) students’ perception towards teaching style, such as teaching method, motivating, giving feedback were almost negative and (2) students’ ideal expectations that an English teacher should be more effective, efficient interactive and creative for creating more interesting classroom atmosphere.  Keywords: Teacher Talk, Perception, Expectation